A conceptual content analysis of English language textbooks concerning Islam and Muslims - Ruzai Syarilili Aiyu bt Abd Rashid (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The changing landscape of English language teaching and learning has compelled English language teaching materials to be culturally sensitive and appropriate to the context in which the language is taught. There is a need to match teaching materials with the goals, objectives and philosophy of a programme and to ensure consistency with learners' attitudes, religious beliefs and/or preferences. In other words, English Language Teaching (ELT) materials must be consistent with the needs and interests of the intended learners, as well as being in harmony with institutional ideologies and religious doctrines. The objectives of the study are to codify ELT materials based on socio-cultural and religious perspectives and to examine features of ELT materials based on the adapted Byram's cultural content list. Five English language textbooks used in the intensive language programme at the International Islamic University Malaysia are analysed based on the conceptual content analysis. The findings reveal that the ELT textbooks are organized based on four main categories; namely, belief and behaviour, socialization and life cycles, stereotypes and national identity and social and political institution. The findings of the study indicate that there are 14 neutral items, eight negative items and one positive item that mention Islam and Muslims. Furthermore, there are 77 items which are found not to be in harmony with Islam ranging from food, drinks, recreation and sports. The findings also suggest that the textbooks are loaded with features of Western culture. While the textbooks are relevant to the learners' culture, teachers need to inform the students that there are differences between Islam and the Judeo-Christian worldview.